Aptamer-Based Planar Electric Double-Layer Field-Effect Transistor: A Novel Approach for Sensitive Troponin I Sensing - Sheng-Chun Hung; Yi-Hua Lee (Biosensors)
This study introduces a cutting-edge, aptamer-based, planar electric, double-layer field-effect transistor (FET) system that offers both high sensitivity and specificity for the detection of troponin I (TnI). The proposed sensing platform leverages the signal amplification capabilities of FETs alongside the unique attributes of a planar electric double-layer design to address the limitations inherent in traditional ion-sensitive detectors, which are impacted by Debye length effects. By integrating TnI-specific aptamers, the system markedly enhances molecular recognition and transduction efficiency, achieving an impressive detection limit of <semantics>0.0001467 decade</semantics>. Furthermore, the sensor demonstrates a strong exponential linear response across a clinically relevant concentration range of 1 ng/mL to 100 ng/mL. This innovative approach underscores the potential of electric double-layer FET systems to advance biomarker detection technologies for medical diagnostics and point-of-care applications.